Downregulation of the RECK-tumor and metastasis suppressor gene in glioma invasiveness - Correa, Tatiana C. Silveira; Brohem, Carla Abdo; Winnischofer, Sheila Maria Brochado; Cardeal, Laura Beatriz da Silva; Sasahara, Regina Maki; Taboga, Sebastio Roberto; Sogayar, Mari Cleide; Maria-Engler, Silvya Stuchi (Wiley-Blackwell, 2006)
Invasive behavior is the pathological hallmark of malignant gliomas, being responsible for the failure of surgery, radiation, and chemotherapy. Matrix metalloproteinases (MMPs) are essential for proper ECM remodeling and invasion. The tumor and metastasis suppressor RECK protein regulates at least three members of the MMPs family: MMP-2, MMP-9, and MT1-MMP. In order to mimic the in vivo invasion process, A172 and T98G, respectively, non-invasive and invasive human glioblastoma cell lines, were cultured onto uncoated (control) or type I collagen gel-coated surface, and maintained for up to 7 days to allow establishment of the invasive process. We show that the collagen substrate causes decreased growth rates and morphological alterations correlated with the invasive phenotype. Electronic transmission microscopy of T98G cells revealed membrane invaginations resembling podosomes, which are typically found in cells in the process of crossing tissue boundaries, since they constitute sites of ECM degradation. Real time PCR revealed higher RECK mRNA expression in A172 cells, when compared to T98G cells and, also, in samples obtained from cultures where the invasive process was fully established. Interestingly, the collagen substrate increases RECK expression in A172 cells and the same tendency is displayed by T98G cells. MMPs-2 and -9 displayed higher levels of expression and activity in T98G cells, and their activities are also upregulated by collagen. Therefore, we suggest that: (1) RECK down regulation is critical for the invasiveness process displayed by T98G cells; (2) type 1 collagen could be employed to modulate RECK expression in glioblastoma cell lines. Since a positive correlation between RECK expression and patients survival has been noted in several types of tumors, our results may contribute to elucidate the complex mechanisms of malignant gliomas invasiveness.
Keywords: RECK; MMPs; collagen; glioma